Ionic liquids with thioether motifs as synthetic cationic lipids for gene delivery. Issue 59 (10th July 2017) - Gaitor, Jamie C.; Paul, Lauren M.; Reardon, Melissa M.; Hmissa, Taha; Minkowicz, Samuel; Regner, Matthew; Sheng, Yinghong; Michael, Scott F.; Isern, Sharon; Mirjafari, Arsalan
Abstract : Novel lipidic ionic liquids with imidazolium headgroups (red), thioether linkers (black), and two hydrophobic tails (blue) as efficient gene transfection vectors, synthesized via thiol–yne click chemistry. Abstract : This study introduces a novel class of imidazolium- and ammonium-based ionic liquids possessing two C12 and C14 tails and thioether linkers designed for lipoplex-mediated DNA delivery. Imidazolium-based ionic liquids displayed efficient gene delivery properties with low toxicity. Thiol–yne click chemistry was employed for the facile and robust synthesis of these thioether-based cationic lipioids with enhanced lipophilicity and low fluidity.